Pengaruh Pengalaman Mengajar dan Motivasi Kerja Terhadap Guru Biologi Tersertifikasi Di SMA Negeri Se-Kota Palu - Tangge1, Lilies; Ferlin2, Alfira (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Quality of education can be realized if the learning process takes place properly. Success in education is highly determined by the teacher performance. Teacher performance can be affected by several factors such as the length of teaching experience which often attend the training and work motivation whether in intrinsic or extrinsic that will be produced qualified learners. This research aims to describe the impact of teaching experience and work motivation to the performance of biology teacher certification of SMA Negeri in Palu and to depict the impact of teaching experience and work motivation simultaneously to the performanceÂ  of biology teacher certification of SMA Negeri in Palu. The method of the research was survey with descriptive quantitative approach. The sampling technique was saturated sampling technique which the entire population used as a sample. Observation variable were teaching experience, work motivation and teacher performance. The research instrument was questionnaire with multiple regresission analysis technique. The result of the research showed that teaching experience has a significant impact on the performance of certified biology teacher with value 0,001, work motivation has a significant impact on the performanceof certified biology teacher with value 0,000, teaching experience and work motivation concurrently have significant impact on teacher performance of certified biology teacher with value 0,000.